Effect of the Time-Varying Damping on the Vibration Isolation of a Quasi-Zero-Stiffness Vibration Isolator - Xin Li; Jinqiu Zhang; Jun Yao (Shock and Vibration)
This study focuses on the effect of damping changes on the vibration isolation of a quasi-zero-stiffness vibration isolator. A nonlinear-vibration equation for the quasi-zero-stiffness vibration isolator is found and solved using the multiscale method. Then, the vibration characteristics before, in the process of and after the damping change, are also examined. The results show that time-varying damping can be equivalent to the addition of a stiffness term to the vibration system, which leads to a change of the vibration amplitude frequency response, leakage of power spectrum, and corresponding linear spectrum features being weakened. When the damping changes rapidly, the vibration system tends to be divergent rather than stable. After the change, the number of stable focuses of the proposed quasi-zero-stiffness vibration isolator increases from one to two, and the system will see decline in its vibration stability.